"55 Common MistakesYou Often Do in C++ Programming (Who says programming is difficult?)" - Rashidah Mokhtar; Safura Adeela Sukiman; Azrina Suhaimi; Mohd Lezam Lehat; Rohaizan Ramlan (Penerbit UTHM, 2022)
This book aims to expose learners to common mistakes done while writing C++ programming language codes. This book covers the fundamentals of C++ programming language which relate to basic C++ concepts such as basic elements of C++, selection, looping, function and array and it is associated with structured programming. This book is compiled based on the authors’ experience who had taught C++ programming for more than 7 years. It is the common syntax errors that are often done by students. This is the reason why this book is produced in the first place. This book also includes tips on how to avoid the mistakes by showing the correct syntax. The book is made up of 14 sections, each showing various errors and its correction. For each error there is a solution on the correct syntax. This book also employs simple English; this makes it one of the must-have guide book for beginners. Hopefully, this book will prove beneficial to all learners especially to beginner of C++ language.